THE RELATIONSHIP BETWEEN PARENTING STYLE AND DEPRESSION AMONG ADOLESCENTS - Olutunde, Olatunji Samuel (IJRDO- Journal of Educational Research, 2017)
This study examines the relationship between parenting style and depression among adolescents.Parenting style was grouped into three categories viz; Authoritarian, Permissive andAuthoritative. Three non-directional hypotheses were formulated to answer the researchquestions raised in this study. The first hypothesis states that there will be a significantrelationship between authoritarian parenting style and depression among adolescents. The secondhypothesis states that there will be a significant relationship between permissive parenting styleand depression among adolescents. The third hypothesis states that there will be a significantrelationship between authoritative parenting style and depression among adolescents. A samplesize of 180 participants comprising 90 male and 90 female between ages 12 – 18 years drawnfrom SS2 students of five Secondary Schools in lkare-Akoko,Ondo State, Nigeria respectivelyresponded to Self – rating Depression Scale [SDS] and Parental Care Scale [PCS]. Participants’scores were subjected to analysis with Hierarchical Multiple Regression analysis and result shows that; Authoritarian parenting style has a significant relationship with depression amongadolescents. Permissive parenting style also has a significant relationship with depression amongadolescents. Authoritative parenting style has a significant relationship with depression amongadolescents. Based on these findings, the present study has demonstrated that a significantrelationship actually exist between parenting style and depression among adolescents. Thepresent study recommended that adolescents should be given the necessary assistance so thatthey will be able to cope with the stressors that accompany living in either of the three parentingstyle.